Impacts of community participation, multi-actor collaboration, transparency, and accountability on village financial governance in Rokan Hulu, Indonesia - Susanti, Delpi; Sujianto, Sujianto; Tua, Harapan; As’ari, Hasim; Yulia, Dinda (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
This study examines the impact of community participation, multi-stakeholder collaboration, transparency, and accountability on village financial governance policies in Rokan Hulu Regency, Riau Province, within the framework of the New Public Governance (NPG) paradigm. This research used a mixed methods approach with a sequential exploratory design. Qualitative data were collected through semi-structured interviews, direct observation and document analysis, then analyzed using thematic techniques. Quantitative data was obtained through a Likert scale questionnaire survey involving 90 purposively selected respondents and analyzed descriptively and inferentially. The research findings show that community participation, multi-stakeholder collaboration, transparency, and accountability significantly improve the effectiveness, efficiency, and accountability of village financial governance. However, challenges such as low participation of vulnerable groups, weak synergy between informal actors, and unequal access to information are still major obstacles. The study concludes that strengthening formal collaboration, improving technical capacity through internal audit training, and adopting inclusive strategies to increase community participation are critical to advancing village financial governance. This study contributes to the theoretical development of the NPG paradigm and provides practical recommendations for designing policies for inclusive and sustainable village financial governance.